Type, Rather than Number, of Mental and Physical Comorbidities Increases the Severity of Symptoms in Patients with Irritable Bowel Syndrome - Lackner, Jeffrey M. (2013)
BACKGROUND: Irritable bowel syndrome (IBS) has significant mental and physical comorbidities. However, little is known about the day-to-day burden these comorbidities place on quality of life (QOL), physical and mental function, distress, and symptoms of patients. METHODS: We collected cross sectional data from 175 patients with IBS, diagnosed based on Rome III criteria (median age, 41 y; 78% women), referred to 2 specialty care clinics. Patients completed psychiatric interviews, a physical comorbidity checklist, the IBS symptom severity scale, the IBS quality of life instrument, the brief symptom inventory, the abdominal pain intensity scale, and the SF-12 health survey. RESULTS: Patients with IBS reported an average of 5 comorbidities (1 mental, 4 physical). Subjects with more comorbidities reported worse QOL after adjusting for confounding variables. Multiple linear regression analyses indicated that comorbidity type was more consistently and strongly associated with illness burden indicators than disease counts. Of 10, 296 possible physical–mental comorbidity pairs, 6 of the 10 most frequent dyads involved specific conditions (generalized anxiety, depression, back pain, agoraphobia, tension headache, insomnia). These combinations were consistently associated with greater illness and symptom burdens (QOL, mental and physical function, distress, more severe symptoms of IBS, pain). CONCLUSIONS: Comorbidities are common among patients with IBS. They are associated with distress and reduced QOL. Specific comorbidities are associated with more severe symptoms of IBS.